Associations of methods of suicide attempts with mental disorders and self-esteem in adults attended in health establishments in Metropolitan Lima, 2015 - Alva barreto, Carolina (2025)
In Peru, 1 out of 20 people has experienced a suicide attempt at some point in his/her life, and in Lima, a person attempts suicide every 22 minutes. The method of attempted suicide is an important factor to be considered among a series of suicide prevention measures. Objective: To determine the association of suicide attempt methods with sociodemographic factors, mental disorders and self-esteem in adults attended in health establishments in Metropolitan Lima - 2015. Materials and methods: Analytical cross-sectional study, of probabilistic type, with analysis of a database obtained from the Epidemiological Study of Mental Health in general hospitals and health centers of Metropolitan Lima - 2015. Suicide attempt methods will be described according to demographic characteristics and poverty level using contingency tables, indicators and statistical graphics. Results: A female predominance was found (78.4%), with an average age of 39.9 ± 14.4 years. The most used suicide method was the consumption of a toxic substance (59.2%). A significant association was found between the suicidal method and sex (p < 0.001), age (p = 0.001), educational level (p = 0.003), marital status (p < 0.001) and the presence of a mental disorder (p = 0.035). Conclusions: The associations found in this study are consistent with those found in previous studies, marital status standing out among them. It is hoped that the results can help in the management of people at risk of a suicidal attempt.